2013
DOI: 10.1530/joe-13-0210
|View full text |Cite
|
Sign up to set email alerts
|

Mitotane reduces human and mouse ACTH-secreting pituitary cell viability and function

Abstract: Medical therapy for Cushing's disease (CD) is currently based on agents mainly targeting adrenocortical function. Lately, pituitary-directed drugs have been developed, with limited efficacy. Mitotane, a potent adrenolytic drug, has been recently investigated for the treatment of CD, but the direct pituitary effects have not been clarified so far. The aim of our study was to investigate whether mitotane may affect corticotroph function and cell survival in the mouse pituitary cell line AtT20/D16v-F2 and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Mitotane was of higher importance in the earlier period of our study before the development of targeted pituitary-directed medications. In addition to its well known adrenolytic ac- tivity, there are published data supporting potential action on a pituitary level [50]. All our patients treated with an adjuvant therapy with mitotane after PRT or TSA achieved a remission.…”
Section: Blockers Of Steroidogenesissupporting
confidence: 55%
“…Mitotane was of higher importance in the earlier period of our study before the development of targeted pituitary-directed medications. In addition to its well known adrenolytic ac- tivity, there are published data supporting potential action on a pituitary level [50]. All our patients treated with an adjuvant therapy with mitotane after PRT or TSA achieved a remission.…”
Section: Blockers Of Steroidogenesissupporting
confidence: 55%
“…The effect of Staurosporine, a well known apoptotic stimulus, on cell viability was assessed by measuring cellular ATP levels using the ATPLite luminescence-based assay (PerkinElmer, Waltham, MA, USA) following manufacturer’s instructions and reading the plate with the EnVision Multilabel Reader (PerkinElmer) as previously described [16,17]. Briefly, 2 x 10 4 cells/ well were plated in optically clear 96-well black plates (Costar #3904, Corning, NY, USA) and incubated overnight at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…ACTH levels were found to be scattered with great individual variations. More recently, Gentilin et al (17) showed that mitotane was able to affect corticotroph function and cell survival in the mouse pituitary cell line AtT20/D16v-F2 and in the primary cultures of human ACTH-secreting pituitary adenomas. Mitotane reduced cell viability and ACTH secretion by blocking the stimulatory effects of corticotropin releasing hormone (CRH) on cell viability, ACTH secretion and POMC expression.…”
Section: Introductionmentioning
confidence: 99%